Qualitative data analysis with NVivo / Jenine Beekhuyzen, Pat Bazeley. - Beekhuyzen, Jenine, 1974-; Bazeley, Patricia (Sage, 2025)
Straightforward and insightful, this is the go-to book for any qualitative researcher who wants to use NVivo to conduct robust data analysis.